(untitled) (Revista Interdisciplinar de Marketing, 2023)
Marketing has become a vibrant academic field and a highly popular university subject choice globally since Philip Kotler (1967) first popularised the discipline with his seminal text Marketing Management: Analysis, Planning and Control. The normative, managerial paradigm popularised by Kotler remains the dominant influence in marketing thought and pedagogy, yet it has many shortcomings, one of which is the fact that it was conceived for a very different world to the one we now face. In this Pensata I argue that Marketing pedagogy must be conceived as an intellectually critical discipline if it is to serve the needs of contemporary students, organisations and universities. In order to be an intellectually critical discipline, I suggest that Marketing must engage critically with its own ideological character if it is to equip students with the skills to navigate their path through an ideologically inflected world.